2020
DOI: 10.3389/fmars.2020.00231
|View full text |Cite
|
Sign up to set email alerts
|

A High Precision Method for Calcium Determination in Seawater Using Ion Chromatography

Abstract: Calcium (Ca 2+) is an important major cation in seawater, which is closely related to the oceanic biogeochemistry cycle. Direct and accurate determination of Ca 2+ concentration is required for a more comprehensive study of the carbonate system in seawater. Due to the high background concentration of Ca 2+ in seawater and small variances of Ca 2+ during CaCO 3 precipitation and dissolution process, a precision of better than 0.1% (of approximately ± 10 µmol/kg) is very much desired for carbonate chemistry rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, while the values in that table are derived from historic data ( see Millero et al 2008; Table 2), they represent a chemical construct, that is, a model of IAPSO that relates its conductivity to the Practical Salinity Scale, but not its exact composition. In fact, He et al (2020) recently showed, in the context of designing a high‐precision method for measuring seawater Ca concentrations, that the composition of IAPSO varies significantly from batch to batch, a fact also discussed by Pawlowicz (2010). Steiner et al (2020) used a single batch of IAPSO to prepare their calibration standards and derived its Sr/Ca ratio via TIMS with double‐spike ID as 8.545 ± 0.021 mmol mol −1 .…”
Section: Normalization and The Problem Of The Seawater Reference Standardmentioning
confidence: 87%
“…However, while the values in that table are derived from historic data ( see Millero et al 2008; Table 2), they represent a chemical construct, that is, a model of IAPSO that relates its conductivity to the Practical Salinity Scale, but not its exact composition. In fact, He et al (2020) recently showed, in the context of designing a high‐precision method for measuring seawater Ca concentrations, that the composition of IAPSO varies significantly from batch to batch, a fact also discussed by Pawlowicz (2010). Steiner et al (2020) used a single batch of IAPSO to prepare their calibration standards and derived its Sr/Ca ratio via TIMS with double‐spike ID as 8.545 ± 0.021 mmol mol −1 .…”
Section: Normalization and The Problem Of The Seawater Reference Standardmentioning
confidence: 87%
“…In nature, calcium is considered an easily available element as it is among the most abundant cations in water and soil. Nevertheless, concentrations of Ca 2+ ions vary depending on the environment, typically reaching ~10 mM in open ocean water ( 33 ) and ranging between 0.01 and ~1.9 mM in freshwater, with the average at ~0.1–0.35 mM and much higher concentrations observed in the vicinity of carbonate rocks ( 34 ). Calcium concentrations in the soil solutions were reported to reach up to 20 mM ( 35 ) and strongly depend on the type of soil.…”
Section: Discussionmentioning
confidence: 99%
“…B. belcheri xiamen has 25 EF-CaBP genes, B. belcheri beihai has 19 genes, B. floridae has 17 genes, and B. lanceolatum has only 12 genes. Marine salinity is linearly correlated with the calcium ion concentration (He et al 2020). Therefore, we further explored the relationship of the gene number variation of these proximally arrayed EF-CaBP genes and the sea surface salinity of the collection locations (Fig.…”
Section: Calcium Balancementioning
confidence: 99%